Jeju Island : reaching to the core of beauty. - Han'guk Kukche Kyoryu Chaedan (Seoul : Korea Foundation : Seoul Selection, 2011)
'Outside of Korea, Jeju remains a mystery largely because so very little has been written about it in English. This book seeks to rectify that dearth of information, and to share the wonders of Jeju Island with the world.'--p.7.
Includes bibliographical references (pages 139-140)
Keywords: Cheju Island (Korea) -- Description and travel